Energy-efficient building systems green strategies for operation and maintenance - Jayamaha, Lal (McGraw-Hill, 2007)
Property and facility managers can turn to Energy-Efficient Building Systems as a one-stop guide to operating and maintaining commercial building systems at peak efficiency. Designed to help reduce energy costs and meet environmental standards, this state-of-the-art productivity tool contains fully illustrated, real-world examples of successful green building projects that have achieved significant, energy-saving results. From energy management and auditing, HVAC systems, cooling towers, and pumping systems...to lighting, electrical systems, automation, and building envelope, this expert resource takes readers step by step through procedures for getting optimal performance from every building system. For each system, the book presents the latest methods for improving efficiency...identifying promising new solutions...evaluating their feasibility...and estimating actual savings.